(N), C, N‐Coordinated Heavier Group 13–15 Compounds: Synthesis, Structure and Applications. Issue 10 (19th October 2020) - Dostál, Libor; Jambor, Roman; Aman, Michal; Hejda, Martin
Abstract: The aim of this review is to summarize recent achievements in the field of (N), C, N ‐coordinated group 13–15 compounds not only regarding their synthesis and structure, but mainly focusing on their potential applications. Relevant compounds contain various types of N ‐coordinating ligands built up on an ortho‐ (di)substituted phenyl platform. Thus, group 13 and 14 derivatives were used as single‐source precursors for the deposition of semiconducting thin films, as building blocks for the preparation of high‐molecular polymers with remarkable optical and chemical properties or as compounds with interesting reactivity in hydrometallation processes. Group 15 derivatives function as catalysts in the Mannich reaction, in the allylation of aldehydes or activation of CO2 . They were used as transmetallation reagents in transition metal catalysed coupling reactions. The univalent species serve as ligands for transition metals, activate alkynes or alkenes and are utilized as catalysts in the transfer hydrogenation of azo‐compounds. Abstract : ( N ), C, N ‐coordinated group 13–15 compounds : This review summarizes recent achievements in the field of (N), C, N ‐coordinated heavier main group (13–15) compounds built up on an (ortho), ortho‐ (di)substituted phenyl platform. The main emphasis is given on their potential applications in various fields of chemical research including organic synthesis, catalysis, material, polymer and biological science or their utilization as non‐conventional ligands for transition metals.